2017
DOI: 10.1016/j.biopsycho.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electrophysiological correlates of cognitive control in ex-obese adults

Abstract: Impaired cognitive control functions have been documented in obesity. It remains unclear whether these functions normalize after weight reduction. We compared ex-obese individuals, who successfully underwent substantial weight loss after bariatric surgery, to normal-weight participants on measures of resistance to interference, cognitive flexibility and response inhibition, obtained from the completion of two Stroop tasks, a Switching task and a Go/NoGo task, respectively. To elucidate the underlying brain mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that overweight/obese individuals have a longer RT to food-related words, which suggests that there is attentional bias towards food-related words in overweight/obese individuals [25,43]. In addition, researchers used a verbal and a spatial version of the Stroop task and found that there was group difference in the verbal Stroop task between the overweight and normal-weight individuals [44], which might suggest that the OWs’ ability to monitor verbal conflict is more easily damaged. In our study, RT in OWs was significantly longer than that in NWs, which suggested that conflict control was decreased in the OWs, compared to the NWs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that overweight/obese individuals have a longer RT to food-related words, which suggests that there is attentional bias towards food-related words in overweight/obese individuals [25,43]. In addition, researchers used a verbal and a spatial version of the Stroop task and found that there was group difference in the verbal Stroop task between the overweight and normal-weight individuals [44], which might suggest that the OWs’ ability to monitor verbal conflict is more easily damaged. In our study, RT in OWs was significantly longer than that in NWs, which suggested that conflict control was decreased in the OWs, compared to the NWs.…”
Section: Discussionmentioning
confidence: 99%
“…Although standardized electrophysiological methods for people with obesity are not established, previous studies revealed various alterations in ERP components in the people with obesity [22252627]. Appetizing food images triggered larger P100 and P300, relative to control images in obese and non-obese adolescents [4].…”
Section: Discussionmentioning
confidence: 99%
“…The N2 component is associated with inhibitory control [25]. Developmental trajectory of NoGo N2 showed that amplitude and latency of NoGo N2, decreases across the normal childhood period, and that NoGo N2 amplitude was more negative than Go N2.…”
Section: Discussionmentioning
confidence: 99%
“…The Go/No-go task (GNG) was adapted from a previous study [ 36 ] and implemented in Psytoolkit as the IGT. In this task, participants were presented with a series of squares on the center of the screen.…”
Section: Methodsmentioning
confidence: 99%